Eragon - Paolini, Christopher (New York Alfred A. Knopf, 2003)
In Aagaesia, a fifteen-year-old boy of unknown lineage called Eragon finds a mysterious stone that weaves his life into an intricate tapestry of destiny, magic, and power, peopled with dragons, elves, and monsters.
Published in hard cover by Alfred A. Knopf in 2003.
Keywords: Fantasy; Dragons -- Fiction